Experimental study on the dispersed phase macro-mixing in an immiscible liquid–liquid stirred reactor. (14th April 2015) - Cheng, Dang; Feng, Xin; Cheng, Jingcai; Yang, Chao; Mao, Zai-Sha
Abstract: The spatial nonuniformity of solute concentration in the dispersed phase of immiscible liquid–liquid dispersion is smeared out by coalescence and breakup of drops, which has a very significant effect on the productivity of relevant chemical processes. Novel experiments have been designed to visualize and quantify accurately the macro-mixing within the dispersed phase using the planar laser induced fluorescence (PLIF) method combined with a refractive index matching technique in this work. Batch experiments are carried out in a stirred reactor for an electrolytic solution dispersed in silicone oil. It is revealed that the dispersed phase macro-mixing behavior differs much from that of the continuous phase of multiphase systems and is heavily dependent upon the drop interaction rate and thus power consumption. The dispersed phase mixing time decreases with the increase of the dispersed phase volume fraction. Dispersed phase mixing time varies inversely with the power consumption per unit volume dispersion. The effect of impeller type on the dispersed phase mixing time is greatly different from that on the continuous/single phase mixing time. The effect of radial impeller clearance on the dispersed phase mixing time is contrary to that on the continuous/single phase mixing time. Graphical abstract: Highlights: Novel experiment is designed to quantify the macro-mixing of a dispersed phase. Dispersed phase macro-mixing behavior differs from that of the continuous phase. Effect of impeller type is different to that on the continuous phase macro-mixing. The dispersed phase mixing time increases as the impeller clearance decreases. The dispersed phase mixing time decreases with the increase of the dispersed phase.